2009
DOI: 10.7205/milmed-d-04-2608
|View full text |Cite
|
Sign up to set email alerts
|

Female Soldiers’ Gynecologic Healthcare in Operation Iraqi Freedom: A Survey of Camps With Echelon Three Facilities

Abstract: Gaps remain in predeployment gynecologic screening and counseling. These critical predeployment medical evaluations must remain a priority for all female soldiers to ensure unit readiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 6 publications
1
39
0
Order By: Relevance
“…52 Rates of cervical cancer screening among active duty servicewomen have increased over time from 78% of women receiving screening within 12 months of deployment in 2003 to 90% receiving screening in 2005. 53,54 In a large survey of active duty personnel conducted by the DOD in 2005, 97% of military women reported receiving cervical cancer screening within the past 3 years. 17 High rates of cervical cancer screening have also been reported among TRICARE Prime beneficiaries, of whom 92% received screening within the past 3 years.…”
Section: Cervical Cancer Screening and Hpv Vaccinationmentioning
confidence: 99%
“…52 Rates of cervical cancer screening among active duty servicewomen have increased over time from 78% of women receiving screening within 12 months of deployment in 2003 to 90% receiving screening in 2005. 53,54 In a large survey of active duty personnel conducted by the DOD in 2005, 97% of military women reported receiving cervical cancer screening within the past 3 years. 17 High rates of cervical cancer screening have also been reported among TRICARE Prime beneficiaries, of whom 92% received screening within the past 3 years.…”
Section: Cervical Cancer Screening and Hpv Vaccinationmentioning
confidence: 99%
“…Several studies found that contraceptive use decreased during deployment, with proportions of users ranging from 39% to 77% [11]. A study of women deployed to Iraq and Kuwait showed a significant decrease in contraception use during compared to before deployment [12], and another recent study from Iraq had similar findings [13]. The most common methods used during deployment were oral contraceptives (28%-41%), injectables (11%-14%), surgical methods (5%-11%), implants (6%) and patches (5%-6%) [11].…”
Section: Introductionmentioning
confidence: 63%
“…Although surveys show over two-thirds of women have a favorable opinion of and use some form of contraception, the majority use short-acting methods that become difficult to maintain during deployment such as pills (requiring daily use and refills) or patches that fall off from dust and heat. 13,4143 Many factors impacting the lack of contraception use among active duty women have been identified in the literature. These include lack of availability of chosen method while deployed, limited space in barracks for storage and privacy of contraception, and limited health care provider knowledge of contraception.…”
Section: Discussionmentioning
confidence: 99%
“…Active duty women have low percentages of contraceptive use and this nonuse increases during deployment despite having readily accessible health care. 1013 Given that active duty women and Department of Defense (DoD) beneficiaries have access to no cost contraception, this population could potentially serve as a model for an enhanced access to care environment. The impact of unintended pregnancy on mission readiness makes it a women’s health issue of paramount importance.…”
Section: Introductionmentioning
confidence: 99%